Molecular and Pathotype Identification of Potato Cyst Nematodes - Mulyadi Mulyadi; Siwi Indarti; Bambang Rahayu T.P.; B. Triman (Universitas Gadjah Mada, 2014)
In Indonesia, potato cyst nematode (PCN) was first reported in Bumiaji, Kota Batu, East Java by PT Syngenta and was identified as Globodera rostochiensis. Based on the surveillances, G. rostochiensis were also found in Batur, Banjarnegara, and Kejajar, Wonosobo, and Pangalengan, Bandung. In addition, in Batur, Banjarnegara, another species which was identified as G. pallida was found. The aim of this research were to identify the species of PCN using molecular method, pathotype identification, and to study the distributions of PCN especially in Java. The PCN are collected from potato planting areas in Kota Batu, East Java; Wonosobo and Banjarnegara, Central Java; and Pangalengan, Bandung, West Java. PCN were extracted and isolated from soil, and then identified by morphological and molecular analysis. PCN were found in potato planting areas in Kota Batu, East Java; Wonosobo and Banjarnegara, Central Java; and Pangalengan, West Java. Based on the morphological characters, molecular method, and the differential host test, the PCN identified as G. rostochiensis are amplified an approximately 434 bp with pathotype Ro2. Di Indonesia, nematoda sista kentang (NSK) pertama dilaporkan di Bumiaji, Kota Batu, Jawa Timur oleh PT Syngenta yang diidentifikasi sebagai Globodera rostochiensis. Berdasarkan hasil survei, NSK ditemukan di Batur, Banjarnegara dan Kejajar, Wonosobo, Pangalengan. Spesies G. pallida juga ditemukan Batur, Banjarnegara. Penelitian ini bertujuan untuk mengidentifikasi spesies NSK menggunakan metode molekuler, identifikasi patotipe NSK, dan untuk mengetahui penyebaran NSK khususnya di Pulau Jawa. Sampel NSK dikumpulkan dari lahan pertanaman kentang di Bumiaji, Kota Batu, Jawa Timur; Wonosobo dan Banjarnegara, Jawa Tengah; serta Pangalengan, Bandung, Jawa Tengah. NSK diekstraksi dan diisolasi dari tanah yang selanjutnya diidentifikasi secara morfologi dan analisis molekuler. NSK yang terdapat pada lahan pertanaman kentang ditemukan di Kota Batu, Jawa Timur; Wonosobo dan Banjarnegara, Jawa Tengah; serta Pangalengan, Jawa Tengah. Berdasarkan karakter morfologi, metode secara molekuler, dan uji kesesuaian inang, NSK yang diperoleh teridentifikasi sebagai G. rostochiensis yang teramplifikasi pada kisaran 434 bp dengan patotipe Ro2.